Activated Functionalized Carbon Nanotubes and 2D Nanostructured MoS2 Hybrid Electrode Material for High‐Performance Supercapacitor Applications. Issue 10 (20th April 2020) - Gupta, Honey; Mothkuri, Sagar; McGlynn, Ruairi; Carolan, Darragh; Maguire, Paul; Mariotti, Davide; Jain, P. K.; Rao, Tata Narasinga; Padmanabham, G.; Chakrabarti, Supriya
Abstract : Alkali‐activated functionalized carbon nanotubes (AFCNTs) and 2D nanostructured MoS2 are investigated as a novel hybrid material for energy‐storage applications. The nanoflower‐like 2D MoS2 is grown on the surface of AFCNT using the controlled one‐step hydrothermal technique. The activation of functionalized carbon nanotubes results in greater performance due to the improved surface area. The Brunauer–Emmett–Teller (BET) surface area of the AFCNTs is found to be 594.7 m 2 g −1 which is almost 30 times of the as‐prepared carbon nanotubes (CNTs). The improved surface area with attached hydroxyl and carboxylic functional groups helps in the attachment of MoS2 nanoflowers onto the AFCNT, thus reducing the interfacial resistance and providing an easy path for electron transfer. The electrochemical analysis shows a high specific capacitance of 516 F g −1 at 0.5 A g −1 with a corresponding energy density of 71.76 Wh kg −1, which is an encouraging reported value from AFCNT and MoS2 hybrid material. To the best of our knowledge, herein, the first report on AFCNTs and 2D MoS2 nanostructured hybrid electrode material for supercapacitor applications is provided, and promising results in terms of specific capacitance, energy density, and power density by boosting the properties of individual material are explained. Abstract : Alkali‐activated functionalized carbon nanotubes (AFCNTs) and 2D nanostructured MoS2 hybrid electrode material for supercapacitor (SC) applications are derived. The SC unveils a high specific capacitance, high energy density, an extremely low charge transfer resistance, and high stability. Herein, opportunities are provided for extending this lab‐scale research to the commercial level for high‐performance SC devices.